STRATEGI PENGEMBANGAN EKONOMI LOKAL BERBASIS KOMODITAS PISANG KEPOK STUDI KASUS DESA NGGILAT KECAMATAN MACANG PACAR, KABUPATEN MANGGARAI BARAT, PROVINSI NTT (Local Economic Development Strategy Based on Kepok Banana Commodity Case Study: Nggilat Village, Macang Pacar District, West Manggarai Regency, NTT Province) - MBINU, MARIA GABRIELA; GUNAWAN, CAKTI INDRA; SANTOSO, T.BUDI (Universitas Mulawarman (University of Mulawarman), 2024)
Nggilat Village, located in Macang Pacar District, West Mangarai Regency, NTT Province, is one of the Kepok Banana producing areas. Bananas are the main commodity for farmers to earn income. The purpose of this study is to analyze the income of banana farmers and to find out the right strategy for Nggilat Village, located in Macang Pacar District, West Mangarai Regency, NTT Province. The study was conducted using interview, observation, questionnaire and documentation methods. The method in this study is SWOT analysis and Farmer analysis. The results showed that Pisang Kepok is worth working on because the income obtained by banana kepok farmers in Nggilat Village is Rp. 42,458,500 per year or Rp. 3,500,000 per month. The value of this income far exceeds the UMR in West Manggarai Regency. The RCR value is 14.93, which means that kepok banana farming in Nggilat Village is worth trying. The strategy used for the development of kepok banana farmers is to use the Growth strategy. Growth Strategy where farmers take advantage of existing strengths and opportunities for the development of existing farmers in this case is the development of kepok bananas in Nggilat Village.